2020
DOI: 10.37496/rbz4920190098
|View full text |Cite
|
Sign up to set email alerts
|

Short-term use of monensin and tannins as feed additives on digestibility and methanogenesis in cattle

Abstract: RuminantsFull-length research article Short-term use of monensin and tannins as feed additives on digestibility and methanogenesis in cattle ABSTRACT -The objective was to assess the effects short-term use of monensin and Acacia mearnsii tannins as feed additives on nutrient intake, digestibility, and CH 4 production in cattle. Six rumen-cannulated Holstein cows were distributed in two 3×3 Latin square experimental design, and each experimental period lasted 21 days. The basal diet was composed of corn silage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Out of 41 papers, 17 articles were excluded for the following reasons: summary papers (4), no CH 4 emission measurements (2), no monensin/treatment effect results reported (2), without control measurements (3), conference papers as there were duplicate publications of the similar study (2), conference paper only reported an abstract, simulation papers (2), and paper that investigated the effects of monensin when mixed with other feed additives. The final database had a total of 24 papers that met the criteria and remained in the database; however, 13 were related to beef cattle [ 29 , 36 , 38 , 39 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 11 were related to dairy cattle [ 8 , 9 , 28 , 30 , 31 , 32 , 33 , 34 , 53 , 54 , 55 ]. Then, beef cattle papers were excluded from the database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 41 papers, 17 articles were excluded for the following reasons: summary papers (4), no CH 4 emission measurements (2), no monensin/treatment effect results reported (2), without control measurements (3), conference papers as there were duplicate publications of the similar study (2), conference paper only reported an abstract, simulation papers (2), and paper that investigated the effects of monensin when mixed with other feed additives. The final database had a total of 24 papers that met the criteria and remained in the database; however, 13 were related to beef cattle [ 29 , 36 , 38 , 39 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 11 were related to dairy cattle [ 8 , 9 , 28 , 30 , 31 , 32 , 33 , 34 , 53 , 54 , 55 ]. Then, beef cattle papers were excluded from the database.…”
Section: Methodsmentioning
confidence: 99%
“…Enteric CH 4 mitigation strategies in ruminants include but are not limited to, dietary feed formulation changes [ 7 ], the use of feed additives/rumen modifiers such as ionophores [ 8 ], essential oils [ 9 ], plants extracts [ 10 ], plant secondary metabolites (e.g., tannins) [ 11 ], and chemical inhibitors [ 12 ] along with genetics and management [ 13 ]. All these strategies have been shown to reduce enteric CH 4 production either directly or indirectly; however, consistent and cost-effective strategies are not yet established [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, testing increasing levels (0, 5, 10, 15, and 20 g/kg of diet DM) of A. mearnsii CTs in the diets of Jersey steers, it was found that the ruminal protozoa population was not affected by CTs, while protein digestibility, ruminal pH, and acetate proportion were decreased [89]. An in vivo study using A. mearnsii extract at 100 g tannin extract cow/day feed supplementation observed that it was less active than the polyether antibiotic monensin in reducing CH 4 emissions or increasing total VFAs [90,91]. Acacia spp.…”
Section: Effect Of Polyphenols On Rumen Fermentation Parametersmentioning
confidence: 99%
“…Stall-fed Holstein cows treated with 18 mg/kg of dry matter monensin showed a 24.3% decline in CH 4 production when expressed in g/day. According to the authors, this reduction could be due to the positive effect of monensin on the Gramnegative bacteria that produce propionate and due to the negative effect of monensin on the acetate and hydrogen-producing bacteria such as Eubacterium, Lactobacillus, and Streptococcus [115]. Likewise, feedlot-type penned Angus steers fed with 33 mg/kg monensin showed a 30% reduction in enteric CH 4 production (measured using the SF6 technique) along with a numeric reduction in ciliated protozoan populations [116].…”
Section: Ionophore Supplementationmentioning
confidence: 99%